2007
DOI: 10.1016/j.ydbio.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of embryonic stem cells into bladder tissue

Abstract: Manipulatable models of bladder development which interrogate specific pathways are badly needed. Such models will allow a systematic investigation of the multitude of pathologies which result from developmental defects of the urinary bladder. In the present communication, we describe a model in which mouse embryonic stem (ES) cells are directed to differentiate to form bladder tissue by specific interactions with fetal bladder mesenchyme. This model allows us to visualize the various stages in the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 26 publications
(39 reference statements)
3
61
0
2
Order By: Relevance
“…Advances in isolation and characterization of tissue-specific SCs will allow further investigation of their differentiation potential and how they are influenced by stromal microenvironments. Our data imply that mammary SCs show a more limited range of differentiation capacity compared with SSCs and ESCs, since under the same experimental conditions, reported by us and others [35], mammary epithelial SCs were unable to fully transform into a prostatic phenotype but instead maintained several of its original differentiation markers, in addition to expressing new ones. In tissue recombinants of other tissue types (including skin, bladder, or esophagus), we showed focal areas of new phenotype (induced by stroma) adjacent to regions of original differentiation markers.…”
Section: Discussionsupporting
confidence: 82%
“…Advances in isolation and characterization of tissue-specific SCs will allow further investigation of their differentiation potential and how they are influenced by stromal microenvironments. Our data imply that mammary SCs show a more limited range of differentiation capacity compared with SSCs and ESCs, since under the same experimental conditions, reported by us and others [35], mammary epithelial SCs were unable to fully transform into a prostatic phenotype but instead maintained several of its original differentiation markers, in addition to expressing new ones. In tissue recombinants of other tissue types (including skin, bladder, or esophagus), we showed focal areas of new phenotype (induced by stroma) adjacent to regions of original differentiation markers.…”
Section: Discussionsupporting
confidence: 82%
“…This is the first report of FOXA1 and IRF-1 localisation in human urothelium, although FOXA1 expression has been demonstrated previously in bladder, prostate and other epithelial tissues in the adult rat, and is expressed throughout the urothelium of the renal pelvis in adult mice 21 and in the developing mouse lung and bladder. [21][22][23] FOXA1 has been proposed to play an important role in the embryonic development and differentiation primarily of endodermally derived tissues, 21,24,25 including urothelium, 44 although there is evidence that FOXA1 and FOXA2 are required for mesoderm formation. 23 Our study showed FOXA1 expression in urothelia from both endodermally derived bladder and mesodermally derived ureter, implying a mutual differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic stem cell-derived endoderm progenitors offer a remarkable potential for the treatment of major diseases affecting the pancreas, liver, lungs, bladder, and prostate [1,2]. Endoderm progenitors would also be useful for the study of congenital diseases [3], gene discovery, toxicology screening, and drug development [4].…”
Section: Introductionmentioning
confidence: 99%